Study of NBI-driven chirping mode properties and radial location by the heavy ion beam probe in the TJ-II stellarator. (19th August 2016) - Melnikov, A.V.; Eliseev, L.G.; Castejón, F.; Hidalgo, C.; Khabanov, P.O.; Kozachek, A.S.; Krupnik, L.I.; Liniers, M.; Lysenko, S.E.; de Pablos, J.L.; Sharapov, S.E.; Ufimtsev, M.V.; et al.
Abstract: Alfvén eigenmodes (AEs) were studied in low magnetic shear flexible heliac TJ-II ( B 0   =  0.95 T, R 0   =  1.5 m, 〈 a 〉   =  0.22 m) neutral beam injection (NBI) heated plasmas ( P NBI   ⩽  1.1 MW, E NBI   =  32 keV) using the heavy ion beam probe (HIBP). L-mode hydrogen plasmas heated with co-, counter- and balanced-NBI and electron cyclotron resonance heating (ECRH) were investigated in various magnetic configurations with rotational transform ι ( a )/2 π   =  1/ q ~ 1.5–1.6. The HIBP diagnostic is capable of simultaneously measuring the oscillations of the plasma electric potential, density and poloidal magnetic field. In earlier studies chirping modes have been observed with 250 kHz  <   f AE   <  380 kHz in combined ECR and NBI heated plasmas at low density n ¯ e   =   (0.3–1.5)  ×  10 19 m −3 . In this paper we report the observation of chirping modes obtained with NBI only in plasmas with densities similar to those of earlier studies and obtained after lithium evaporation in the vacuum vessel. The absence of ECRH in the discharges studied here shows that ECRH is not a necessary ingredient to obtain chirping modes in TJ-II but rather a tool for obtaining low-density discharges. Using the HIBP we deduce that the location of the AE chirping mode is  −0.8  <   ρ   <  0.8. Chirping modes have a specific spatial structure: electric potential perturbations have a ballooning character, while the density and B pol perturbations are nearly symmetric for both ECRH  +  NBI and NBI-only plasmas. On TJ-II, the dominant effect on the nonlinear evolution of the AE from the chirping state to the steady-frequency state is the magnetic configuration, determined by the vacuum ι and plasma current I pl .